Methodological foundations of assessing research impact in business and management - Grzeszczyk, Tadeusz A. (Ekonomia i Prawo. Economics and Law, 2022)
Motivation: Assessment of research impact in the business and management field is more difficult than in the case of Science, Technology, Engineering, and Mathematics (STEM) disciplines and, therefore, it is justified to improve the approaches, methods and tools used in this field and social sciences in general. Methodological research concerning such assessment is quite a challenge as it is not easy to identify useful assessment methods, indicators and evaluation criteria for carrying out objective processes for conceptualizing and measuring research impact. Creating conditions for obtaining reliable results of research impact assessment is accompanied by the growing interest of scientists and public institutions sponsoring their study. Aim: The article aims to indicate the current main methodological trends in assessing the impact of research in business and management. Results: The paper presents the results of bibliometric research enabling the identification of leading study centers and main methodological solutions, which may be a source of progress in the field of research on systems and methods of research impact assessment in business and management. This is especially important for the scientific community and public sponsors from countries that are currently starting to implement impact assessment systems. It is worth drawing from the experience, good practices and vast resources of knowledge related to evaluation systems and models of knowledge exchange between academia and non-academic stakeholders.